The impact of macroeconomic variables on Brusa Stock Exchange using machine learning model - Kok, Yu Chen (2024)
This paper attempts to explore the relationship between four macroeconomic variables on Bursa Stock Exchange using the Machine Learning method. Quarterly data has been used from 2015 quarter 1 until 2022 quarter 4 for all the variables like, overnight policy rate, industrial production index, consumer sentiment index, and unemployment rate. Then, the machine learning method, SHapley Additive Explanation (SHAP) was used to calculate the impact value between stock price and macroeconomic variables. After calculating the impact value, technical indicators were used to test the contribution of macroeconomic variables across the 13 sectors.